Hypervalent iodine promoted the synthesis of cycloheptatrienes and cyclopropanes. Issue 2 (16th December 2021) - Yuan, Da-Fu; Wang, Zi-Chen; Geng, Rui-Sen; Ren, Guang-Yi; Wright, James S.; Ni, Shao-Fei; Li, Ming; Wen, Li-Rong; Zhang, Lin-Bao
Abstract : A new strategy is reported for intramolecular Buchner-type reactions using PIDA as a promotor. Abstract : A new strategy is reported for intramolecular Buchner-type reactions using PIDA as a promotor. Traditionally, the Buchner reaction is achieved via Rh-carbenoids derived from Rh II catalysts with diazo compounds. Herein, the first metal-free Buchner-type reaction to construct highly strained cycloheptatriene- and cyclopropane-fused lactams is presented. The advantage of these transformations is in their mild reaction conditions, simple operation, broad functional group compatibility and rapid synthetic protocol. In addition, scaled-up experiments and a series of follow-up synthetic procedures were performed to clarify the flexibility and practicability of this method. DFT calculations were carried out to clarify the mechanism.